Assessment of the growth in social groups for sustainable agriculture and land management. (2020) - Pretty, Jules; Attwood, Simon; Bawden, Richard; van den Berg, Henk; Bharucha, Zareen P.; Dixon, John; Flora, Cornelia Butler; Gallagher, Kevin; Genskow, Ken; Hartley, Sue E.; Ketelaar, Jan Willem; Kiara, Japhet K.; et al.
Non-technical summary: Until the past half-century, all agriculture and land management was framed by local institutions strong in social capital. But neoliberal forms of development came to undermine existing structures, thus reducing sustainability and equity. The past 20 years, though, have seen the deliberate establishment of more than 8 million new social groups across the world. This restructuring and growth of rural social capital within specific territories is leading to increased productivity of agricultural and land management systems, with particular benefits for those previously excluded. Further growth would occur with more national and regional policy support. Technical summary: For agriculture and land management to improve natural capital over whole landscapes, social cooperation has long been required. The political economy of the later twentieth and early twenty-first centuries prioritized unfettered individual action over the collective, and many rural institutions were harmed or destroyed. Since then, a wide range of social movements, networks and federations have emerged to support transitions towards sustainability and equity. Here, we focus on social capital manifested as intentionally formed collaborative groups within specific geographic territories. These groups focus on: (1) integrated pest management; (2) forests; (3) land; (4) water; (5) pastures; (6) support services; (7) innovation platforms; and (8) small-scale systems. We show across 122 initiatives in 55 countries that the number of groups has grown from 0.50 million (in 2000) to 8.54 million (in 2020). The area of land transformed by the 170–255 million group members is 300 Mha, mostly in less-developed countries (98% groups; 94% area). Farmers and land managers working with scientists and extensionists in these groups have improved both environmental outcomes and agricultural productivity. In some cases, changes to national or regional policy supported this growth in groups. Together with other movements, these social groups could now support further transitions towards policies and behaviours for global sustainability. Social media summary: Millions of geographically based new social groups are leading to more sustainable agriculture and forestry worldwide.